2016
DOI: 10.1111/jace.14194
|View full text |Cite
|
Sign up to set email alerts
|

Triaxial Crystalline Orientation of MgTi2O5 Achieved Using a Strong Magnetic Field and Geometric Effect

Abstract: Tailoring the crystallographic orientation in ceramics is very useful for improving their properties. We reported that the colloidal processing in a strong magnetic field was able to control the crystallographic orientation even in diamagnetic ceramics. In this process, a strong magnetic field is applied to the particles in a stable suspension. The orientation of the crystal depends on the axis having easy magnetization and one‐dimensional orientation can be controlled. In this study, our concept is that contr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 14 publications
0
5
0
Order By: Relevance
“…Many studies have reported the control of its microstructure. 12),21)23) Control of the crystallographic orientation in polycrystalline SiC was achieved by slip casting in a static magnetic field of 12 T. 24) Figure 3 shows the pole figures on the VT plane perpendicular to the magnetic field from the electron back scattering diffraction (EBSD) analysis. The intensity reached maximum at the center, and the c-axis of SiC was aligned parallel to the magnetic field.…”
Section: Easy Magnetization Axis Orientation Based On Static Magneticmentioning
confidence: 99%
See 1 more Smart Citation
“…Many studies have reported the control of its microstructure. 12),21)23) Control of the crystallographic orientation in polycrystalline SiC was achieved by slip casting in a static magnetic field of 12 T. 24) Figure 3 shows the pole figures on the VT plane perpendicular to the magnetic field from the electron back scattering diffraction (EBSD) analysis. The intensity reached maximum at the center, and the c-axis of SiC was aligned parallel to the magnetic field.…”
Section: Easy Magnetization Axis Orientation Based On Static Magneticmentioning
confidence: 99%
“…Next, we attempted to control the tri-axial orientation in MgTi 2 O 5 with an orthorhombic crystal structure. 55) Rodlike MgTi 2 O 5 particles were used as the anisotropic particles, but it was difficult to align the rod-like particles because the particle size and aspect ratio were insufficient to control the alignment of the long sides of rectangular cuboid particles by gravity. Accordingly, tape casting was used for the alignment of the long side of rod-like particles, and one of the short sides was oriented by the magnetic field.…”
Section: Multiaxis Orientation By Combination Of Magnetic Field and Omentioning
confidence: 99%
“…In-field heat treatments (IFT) have been performed in developing the high-performance materials [11][12][13]. In particular, IFT of steel and Fe-C binary alloys have been studied by many researchers, leading to reports on the magnetic-field control of, for example, mechanical properties such as the Vickers hardness [14] and microstructural features such as grain alignment [15].…”
Section: Introductionmentioning
confidence: 99%
“…The oriented green body obtained after slip casting can be further processed to obtain a fully dense textured sample. Such a process has already been successfully applied to oxides, , carbides, nitrides, , and borides, for instance, but rarely applied to TMS. , Indeed, CrSi 2 is a good candidate to demonstrate the usefulness of this texturation method for TE TMS because, to our knowledge, (i) no data is available in the literature on textured polycrystalline samples, (ii) its congruent melting facilitates the synthesis of large amount of material prepared by conventional fusion/solidification processes, and (iii) it has a simple crystal structure compared to other TMS (MnSi 1.74 has an aperiodic crystal structure , and β-FeSi 2 presents stacking faults), which make the realization of texture analyses easier. In this article, the texturation process is first described in detail and the optimal synthesis conditions are discussed.…”
Section: Introductionmentioning
confidence: 99%